Conceptions of nature from the poem “A Folha” by Drummond - Souza, Débora Elisa de; Monteiro, Julia Amorim; Nascimento Junior , Antonio Fernandes (Periódico Eletrônico Fórum Ambiental da Alta Paulista, 2021)
This work aimed to analyze the poem “A Folha”, by Carlos Drummond de Andrade, seeking to identify the ideas of nature that can be enunciated in a Biology teacher training environment. For this, we resorted to Discourse Analysis, using the Bakhtin Circle as a theoretical-methodological framework. From the analysis, it was possible to see that the poem raises dialogues that permeate different ideas of a historically constructed nature, based on the ideas of Plato, Kant, Hegel and Marx and Engels. Furthermore, the analysis of the poem reminds us of the importance of such discussions for teacher education.